Sforza Pallavicino: a Jesuit life in baroque Rome - Delbeke, Maarten (Intersections, 2022)
As a key figure in baroque Rome, Sforza Pallavicino embodies many of the apparent tensions and contradictions of his era: a man of the church deeply involved in the new science, a nobleman and courtier drawn to ascetism and theology, a controversial polemicist involved in poetry and the arts. This volume collects essays by specialists in the fields and disciplines that cover Pallavicino’s activities as a scholar, author and Jesuit, and situate him within the Roman cultural, political and social elite of his times. Through the figure of Pallavicino, an image of baroque Rome emerges that challenges historical periodisations and disciplinary boundaries. Contributors include: Silvia Apollonio, Stefan Bauer, Eraldo Bellini, Chiara Catalano, Maarten Delbeke, Maria Pia Donato, Federica Favino, Irene Fosi, Sven K. Knebel, Alessandro Metlica, Anselm Ramelow, Pietro Giulio Riga, and Jon R. Snyder